The Effect of Documentary Films on Preservice Science Teachers’ Views of Nature of Science - Hakan Şevki Ayvacı; Dilek Özbek (Journal of Science Learning, 2019)
Understanding the nature of science, one of the most important dimensions of scientific literacy, is regarded as an absolute necessity in science education. To teach students the nature of science, science teachers should emphasize the nature of science in the classrooms. This is possible through the training of science teachers with knowledge of the nature of science. In this study, documentary films were used to teach preservice science teachers about the nature of science. This study aims to investigate the effect of nature of science course conducted with documentary films on preservice science teachers’ views of nature of science. The study, in which the experimental design was used, was conducted with 30 preservice teachers in nature of science and history of science courses. Throughout the courses, documentary films were watched, and nature of science aspects of the documentary films was discussed. The Views of Nature of Science Questionnaire (VNOS-C) was used as pre-test and post-test, and the data were analyzed with SPSS. As a conclusion, preservice science teachers’ views regarding the nature of science were enhanced after the implementation.